Disney Does Disney: Re-Releasing, Remaking, and Retelling Animated Films for a New Generation. Issue 3 (3rd July 2022) - Rowe, Rebecca
Abstract: Building from Helena Hammond's discussion of Disney's legacy films, there are three kinds of Disney legacy films designed specifically around Disney's animated classics: legacy re-releases when classic animated films are brought "out of the vault"; legacy remakes which fairly faithfully remake the original animated classics with the story and plot more or less intact; and legacy retellings which draw on animated classics to tell a completely new story, often by focusing on a different perspective or continuing the story beyond the animated classic. These three types of legacy film venerate the Disney company and their catalog in three distinct ways: the re-releases make these films seem like a treasure worth hoarding; the remakes use new technology to give the old films new life, making the original text seem both new and yet always familiar; and the retellings work to show how Disney has supposedly grown as a company, both venerating the original texts and intentionally pointing to their flaws in order to make Disney seem even better today. All three tactics work in concert to bring Disney's past to the present in order to secure their future amidst technological and cultural changes.